PELESTARIAN TRADISI PERKAWINAN ADAT PADA MASYARAKAT SUKU DAYAK KEBAHAN DI DESA ENTOGONG KABUPATEN SINTANG - Ica Paesa Magdalena; F. Y. Khosmas; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2022)
This research aimed to describe as the preservation Community Marriage Tradition in Entogong Village, Kayan Hulu District, Sintang Regency.This research used a qualitative method with a descriptive-ethnographic approach. The data collection techniques used observation, interview and documentation. The data collection tools were observation guidelines, interview guidelines, field notes and documentation tools. The data analysis techniques used data collection, data education, data display and data conclusion. The validity of data, used observations of extended, triangulation of sources and triangulation of techniques. The results of research showing the 1) the process of traditional marriage of the Dayak Kebahan tribe consists of: preparation, groom’s welcome, beduda, ngonyok mandau, nganjan dance, nutok alu beranak, bilang ricek, preparatory worship before blessing, religious blessing procession, ngetok pintu ngamek bini, betopas, buang tabar and mukak tuak pemali. 2) the values of traditional marriage traditions of the Dayak Kebahan tribe is the value of caring for the cooperation, value of religion and value of local wisdom. 3) the role of the Kebahan Dayak community in preserving tradition marriage ceremonies in Entogong vilage such as: mutual cooperation to help the host , pay attention , learn and take part in the activities of traditional marriage ceremonies. There were a friction of the implementation procedure (a) time factors (b) economic factors (c) COVID-19 factores.